Magical contagion and commemorative plaques: Effects of celebrity occupancy on property values. (February 2022) - Ayton, Peter; Weiss-Cohen, Leonardo; Barson, Matthew
Abstract: In many places commemorative plaques are erected on buildings to serve as historical markers of notable men and women who lived in them – London has a Blue Plaque scheme for this purpose. We investigated the influence of commemorative Blue Plaques on the selling prices of London real estate. We identified properties which sold both before and after a Blue Plaque was installed indexing prices relative to the median prevailing sales prices of properties sold in the same neighborhood. Relative prices increased by 27% (US$165, 000 as of July 2020) after a Blue Plaque was installed but not in a control set of properties without Blue Plaques, sold both before and after a Blue Plaque was installed in close proximity. We discuss these findings in relation to the theory of magical contagion and claims from previous research suggesting that people are less likely to acknowledge magical effects when decisions involve money. Highlights: Data on transaction prices of residential properties in London are analyzed. Properties with commemorative plaques signal the residence of notable individuals. Transaction prices of properties increase after commemorative plaques are installed.